BANK OFFICERS’ ROLE IN ANTI-MONEY LAUNDERING DETECTION: A BIBLIOMETRIC REVIEW - Mohamed, Fathimath Sharufa; Yahya, Nurhidayah; Said, Jamaliah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
A significant concern about bank officers’ role in anti-money laundering detection is their limited effectiveness in identifying and reporting suspicious activities, stemming from inadequate training, high workloads, fear of retaliation, overreliance on technology, cognitive biases, inconsistent regulatory compliance, and lack of collaboration, all of which undermine the overall success of AML efforts. Thus, this paper provides a review of bank officers’ roles in anti-money laundering detection from a bibliometric perspective, analysing the Scopus publication database. To guide further research in this area, article titles containing keywords such as “Bank Officers’ Role” OR “Bank Sector” AND “Anti-Money Laundering” OR “Money Laundering” AND “Detection Strategies” OR “AML Detection” OR “Detect” were selected from the database. Following the selection, bibliometric and citation analyses were performed on these documents. Frequency analysis was performed using Microsoft Excel, citation metrics were assessed with Herzing’s Publish or Perish, and data visualisations were achieved through VOS Viewer. The bibliometric study shows a significant increase in research on the role of bank officers in AML detection from 2008 to 2025, fueled by advancements in AI and machine learning. It emphasises overall collaboration, with key contributions from the U.K., U.S., Australia, Malaysia, and Germany. Policy recommendations include promoting technological innovation, fostering international cooperation, strengthening regulatory frameworks, and supporting interdisciplinary research to enhance AML efforts and combat financial crime. The research is confined to the Scopus database and the specific keywords used for the search. Nevertheless, the study has initiated a bibliometric analysis of the vital research area of bank officers’ role in anti-money laundering detection.